Effective control of large deletions after double-strand breaks by homology-directed repair and dsODN insertion - Wei Wen; Zi-Jun Quan; Si-Ang Li; Zhi-Xue Yang; Ya-Wen Fu; Feng Zhang; Guo-Hua Li; Mei Zhao; Meng-Di Yin; Jing Xu; Jian-Ping Zhang; Tao Cheng; et al. (Genome Biology, 2021)
Abstract Background After repairing double-strand breaks (DSBs) caused by CRISPR-Cas9 cleavage, genomic damage, such as large deletions, may have pathogenic consequences. Results We show that large deletions are ubiquitous but are dependent on editing sites and cell types. Human primary T cells display more significant deletions than hematopoietic stem and progenitor cells (HSPCs), whereas we observe low levels in induced pluripotent stem cells (iPSCs). We find that the homology-directed repair (HDR) with single-stranded oligodeoxynucleotides (ssODNs) carrying short homology reduces the deletion damage by almost half, while adeno-associated virus (AAV) donors with long homology reduce large deletions by approximately 80%. In the absence of HDR, the insertion of a short double-stranded ODN by NHEJ reduces deletion indexes by about 60%. Conclusions Timely bridging of broken ends by HDR and NHEJ vastly decreases the unintended consequences of dsDNA cleavage. These strategies can be harnessed in gene editing applications to attenuate unintended outcomes.